Solidarity within limits: Interkit and the evolution of the Soviet Bloc's Indochina policy, 1967–1985. Issue 4 (2nd October 2017) - Szalontai, Balázs
Abstract: This article examines how Interkit, the Soviet-controlled 'anti-China International', evaluated the development of Sino-Indochinese relations, and which contribution the Vietnamese and Laotian delegations made to the forum's meetings. It investigates how the various shifts in Sino-Soviet and Soviet-US relations enhanced or reduced Vietnam's relative importance in Soviet strategy. It describes how the Kremlin sought to dissuade its East European satellites from responding to Beijing's overtures by presenting the Sino-Vietnamese conflict as evidence of China's belligerence, and examines the ideological linkage between Soviet superpower hegemony over Eastern Europe and Vietnamese regional hegemony over Indochina.